Perancangan Sistem Helpdesk Perparkiran Berbasis Web Pada PT Centrepark Citra Corpora dengan Menggunakan Metode Waterfall - Fauzian Abdillah, Muhammad; Ratnasari, Anita (Jurnal Ilmiah Sains dan Teknologi, 2026)
This research aims to design and develop a web-based helpdesk system using the Waterfall software development methodology to streamline data management and operational processes at PT Centrepark, which previously relied on manual systems. The Waterfall method is applied sequentially, starting from requirements analysis, system design, implementation, and system testing to ensure the application meets quality and functionality standards. The system is developed using the PHP programming language, MySQL database, and Laravel framework to support web-based application development. The test results show that the developed information system improves data management efficiency, reduces input errors, and facilitates direct access and reporting of information.